Trends in iron deficiency anemia research 2010 – 2023: a bibliometric analysis - Santosa, Budi; Damayanti, Fitriani Nur; Suparman, Suparman (Universa Medicina, 2024)
Anemia is a health disorder marked by a reduction in hemoglobin concentration (Hb), hematocrit (Ht), and erythrocyte count. Iron deficiency anemia is marked by a reduction in hemoglobin synthesis, resulting in the production of hypochromic microcytic erythrocytes. The interest over time in the topic of iron deficiency anemia throughout the world is increasing. Many studies associated with iron deficiency anemia have been conducted by various authors and are increasing from year to year. The aim of the present review was to evaluate the literature on iron deficiency published between 2010 and 2023, with a focus on the trend in number of publications and citations, the trend of the link strength on the topic of iron deficiency anemia, and the low density of articles published from 2010 to 2023, to determine the trend and novelty of the topic of iron deficiency anemia. This review was a systematic study with the stages conforming to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) diagram. The data on scientific publications on the topic of iron deficiency anemia were collected using dimensions.ai from 2010 to 2023. The data were subsequently analyzed with the Vosviewer program. This review resulted in the following findings. First, the number of publications and citations on the topic of iron deficiency anemia increased exponentially from year to year. Second, there were 139 items, 3 clusters, and 5579 links, with a link strength of 18253 for the topic of iron deficiency anemia. Third, the recommended study topics connected with iron deficiency anemia are topics of low density, namely clinician, pathogenesis, and biofortification. The study findings may assist the interested researchers to know the trends and novelties of studies on iron deficiency anemia, and may recommend suggestions for further research.